2015
DOI: 10.1260/1369-4332.18.4.571
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Segmental Rocking Columns Connected with NiTi Martensitic SMA Bars

Abstract: As well known, the damping or energy dissipation capacity of bridge columns is very important because it is directly related to the design spectrum and affects the seismic performance of whole bridge systems. For this reason, several investigations evaluating the energy dissipation capacity of segmental columns, which has a small energy dissipation capacity itself, have been conducted by adopting various material types of energy dissipating (ED) bars. This paper investigates the damping capacity of post-tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Less plastic hinge damage and substantially lower residual displacement were observed after QSCTs. In addition, PSBCs with UPT and SMA rebar have been proposed to mitigate the residual drift in high seismic regions (Moon et al, 2015), as shown in Table 11.…”
Section: Existing Experimental Investigations Of Precast Segmental Br...mentioning
confidence: 99%
“…Less plastic hinge damage and substantially lower residual displacement were observed after QSCTs. In addition, PSBCs with UPT and SMA rebar have been proposed to mitigate the residual drift in high seismic regions (Moon et al, 2015), as shown in Table 11.…”
Section: Existing Experimental Investigations Of Precast Segmental Br...mentioning
confidence: 99%
“…Unlike rocking RC members where the self-centering and energy dissipation are provided by two separate elements and flexure in the column is minimal, the flag-shaped hysteresis curve of the SMA bars provided both self-centering and energy dissipation to the column models in this study. No studies on flexural-rocking columns of this type were found in the literature, although the shape memory and superelastic properties of SMA have been studied in rocking members (Moon et al, 2015; Nikbakht et al, 2015; Roh and Reinhorn, 2010; Xu et al, 2016).…”
Section: Analytical Investigationmentioning
confidence: 99%
“…Another vital parameter to improve the seismic performance of PSBCs has been the usage of mild steel bars crossing the joints of the precast segments, commonly known as energy dissipation bars (ED bars). These bars have been used in different structural configurations such as exterior energy dissipaters [29][30][31], interior energy dissipation bars [32][33][34][35], and high-strength steel rebars as energy dissipaters [36], with different shapes of piers such as circular [34] and rectangular [37]. The researcher Li and his team investigated the energy dissipation capacities of circular segmental bridge columns based on the experimental models of Hewes and Priestley, and found that increasing the ratio of internal mild steel bars increases the energy dissipation with a rise in the residual drift [14,38].…”
Section: Introductionmentioning
confidence: 99%